2021
DOI: 10.3389/fcvm.2021.591714
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Apheresis as Anti-inflammatory Therapy in Acute Myocardial Infarction: Results of the CAMI-1 Study

Abstract: Background: C-reactive protein (CRP) is a well-known marker of inflammation. It is less known that CRP mediates tissue damage in acute myocardial infarction (AMI) thus potentially worsening prognosis. A newly developed specific CRP adsorber allows efficient lowering of CRP levels and may improve survival.Objectives: Aim of this multi-center, controlled, non-randomized first-in-man CRP apheresis in Acute Myocardial Infarction study (CAMI-1) was to investigate the relationship between CRP levels (CRP gradient), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 54 publications
5
81
0
6
Order By: Relevance
“…CRP concentration kinetics showed a rapid increase in plasma levels between 96 and 132 h after positive SARS-CoV-2 antigen test and 1 st apheresis was then initiated. Apheresis treatments were performed as described elsewhere in detail ( 27 ) and the blood was anticoagulated with ACD-A (1 st apheresis) or ACD-A and additional heparin (2 nd - 4 th apheresis). Treated plasma volume was dependent on patient condition and CRP concentration.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP concentration kinetics showed a rapid increase in plasma levels between 96 and 132 h after positive SARS-CoV-2 antigen test and 1 st apheresis was then initiated. Apheresis treatments were performed as described elsewhere in detail ( 27 ) and the blood was anticoagulated with ACD-A (1 st apheresis) or ACD-A and additional heparin (2 nd - 4 th apheresis). Treated plasma volume was dependent on patient condition and CRP concentration.…”
Section: Case Reportmentioning
confidence: 99%
“…Selective, extracorporeal CRP apheresis with a CRP adsorber ( 25 ) lowers the CRP concentration drastically within a few hours, and the repeatable treatment is safe and efficient ( 26 , 27 ). Clear evidence has been shown in previous clinical studies, investigating CRP apheresis after myocardial infarction, that CRP depletion reduces systemic inflammation and cardiac tissue damage ( 27 ). We used this therapy in the early phase of incipient pulmonary fibrosis in a patient diagnosed with SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, CRP removal was able to significantly reduce infarct size and improve outcomes [ 65 ]. Ries et al, in a pilot study in humans with AMI (CAMI-1 study), reported that CRP apheresis managed to reduce circulating CRP levels and a loss of correlation between CRP levels and infarct size, although CRP reduction was not associated with a significant reduction in infarct size [ 66 ]. However, because CRP increases in a wide variety of other settings, its levels are not sufficiently specific to qualify it as a reliable marker of AMI.…”
Section: Newer Biomarkers For Laboratory Diagnosis Of Acute Myocardial Infarctionmentioning
confidence: 99%
“…According to Świątkiewicz et al, changes in CRP concentrations during STEMI might serve as a risk marker for post-infarct LV systolic dysfunction and heart failure [ 14 , 15 , 16 ], even years after the index event, as well as LV remodeling [ 17 ], underlining the clinical usefulness of CRP dynamics in this patient setting. In the CAMI-1 study, the CRP gradient was suggested to correlate with a greater extent of myocardial infarct size (IS) and reduced LVEF [ 18 ].…”
Section: Introductionmentioning
confidence: 99%